Implementation of Quality Control of Medical Record Services and its Implications for Patient Satisfaction - Felix Kasim (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: High-quality medical records play a crucial role in modern healthcare services as they serve as the primary foundation for medical decision-making and contribute significantly to patient safety and service satisfaction. The success of medical record management is highly dependent on the implementation of effective quality control, which not only includes the accuracy and completeness of data but also ensures that the data is securely managed and easily accessible to healthcare providers. Objective: This study aims to analyze the relationship between the implementation of quality control in medical record services and patient satisfaction at RS Grandmed Lubuk Pakam. Research Methods: This study employs a quantitative descriptive correlational approach. The sample consists of medical record staff and patients, selected through total sampling and purposive sampling techniques. Data was collected through questionnaires and analyzed using Pearson correlation and simple linear regression. Results: The analysis indicates a significant positive relationship between the implementation of quality control and patient satisfaction, with a correlation coefficient of r = 0.652 and a p-value of < 0.05. The regression analysis shows that quality control contributes 42.6% to the variation in patient satisfaction. Conclusion: The better the implementation of quality control in medical record services, the higher the patient satisfaction perceived. Therefore, hospitals need to continue enhancing quality control implementation through staff training, optimization of information technology, and strengthening data protection systems to improve service quality and patient satisfaction.